High prevalence of frailty in end-stage renal disease - Drost, Diederik (Int Urol Nephrol, 2016)
PURPOSE: Prognosis of the increasing number of elderly patients with end-stage renal disease (ESRD) is poor with high risk of functional decline and mortality. Frailty seems to be a good predictor for those patients that will not benefit from dialysis. Varying prevalences between populations are probably related to the instrument used. The aim of this study was to measure the prevalence of frailty among ESRD patients with two different validated instruments. METHODS: This cross-sectional study was conducted among patients, aged ≥18 years, receiving hemodialysis, peritoneal dialysis and pre-dialysis care between September 2013 and December 2013 in a single dialysis center in Apeldoorn, the Netherlands. Frailty was measured with the frailty index (FI) and frailty phenotype (FP). RESULTS: Prevalence of frailty by the FI was 36.8 % among 95 participants with ESRD (age: 65.2 years, SD ± 12.0). Frailty prevalence among participants aged ≥65 and <65 years was 43.6 and 27.5 %, respectively. Female sex [odds ratio (OR) 3.3, 95 % confidence interval (CI) 1.3–8.0] and a Charlson comorbidity index score of ≥5 (OR 2.6, 95 % CI 1.0–6.6) were associated with frailty. The FI identified different but overlapping participants as frail compared with the FP; 62.5 % of frail participants according to FI were also frail according to the FP. CONCLUSIONS: Prevalence of frailty among young and elderly ESRD patients is high; being female and having more comorbidity was associated with frailty. Use of a broader definition of frailty, like the FI, gives a higher estimation of prevalence among ESRD patients compared with a physical frailty assessment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11255-016-1306-z) contains supplementary material, which is available to authorized users.